The Influence of Location and Service Quality on Purchase Decision (Case Study at Rahman Collection Store) - Suleman, Panji; Sahara, Sahara; Cristya, Desty (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of location and service quality on purchase decisions, using a case study at the Rahman Collection Store. A quantitative method was employed, with the research population comprising all railway passengers at Cirebon Station who have interacted with other passengers. The total number of visitors to Rahman Collection Store from July to December was recorded at 21,457. The Slovin formula was used to determine the sample size, resulting in 99.536, which was rounded up to 100 respondents. Data were collected using a Likert scale to measure respondents’ perceptions of the studied variables. The research findings indicate that both location and service quality have a significant influence on consumer purchase decisions. Furthermore, when analyzed jointly, location and service quality were found to simultaneously affect purchasing behavior at the Rahman Collection Store. These results highlight the importance of strategic location and high-quality service in attracting and retaining customers.